HUBUNGAN INTERDEPENDENSI ANTARA STRUKTUR KEPEMILIKAN, RISIKO, KEBIJAKAN HUTANG DAN KEBIJAKAN DIVIDEN DALAM MENJELASKAN TEORI KEAGENAN (Studi Di Bursa Efek Indonesia) - , Arif Afendi, SE ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study examines interdependence relationship between managerial ownership structure, risks, debt policy and dividend policy in explaining agency theory. Agency theory argues that managerial ownership structure, debt policy and dividend policy can be used as a mechanism in taking control of any agency conflict. The sample used in the study was a manufacturer publishing and listing its shares at Indonesia Stock Market in 2004-2009. This study used Three Stage Least Square method to examine the interdependence relationship between managerial ownership, risk, debt policy and dividend policy. The findings showed that there was an interdependence relationship between managerial ownership, risk, debt policy and dividend policy, but no interdependence relationship between risk with debt policy and dividend policy. Furthermore, it also revealed that there was complementary relationship between managerial ownership with debt policy and dividend policy. On the other hand, there was substitutional relationship between debt policy and dividend policy in terms of controlling agency conflict.